UTICAJ KONTROLNIH VARIJABLI NA PREDUZETNIČKE NAMERE KOD ZAPOSLENIH OSOBA - Mali, Predrag; Kuzmanović, Bogdan; Nikolić, Milan; Mitić, Siniša; Terek, Edit (The European Journal of Applied Economics, 2021)
The paper presents the results of the study of individual entrepreneurial orientation dimensions, the achievement dimension and the theory of planned behavior dimensions, depending on seven control variables: the respondents' gender, their age, the educational level of the respondents, the ownership structure of the enterprises, the respondents' previous experience in entrepreneurship, their perceived job performance, and their perceived finances. The specificity of the research is that the respondents are employed persons. The sample included 540 respondents from 72 organizations in Serbia. Data analysis was performed via a t-test. A statistically significant difference in the influence of the observed control variables exists in most cases, except for the control variable - the respondents' level of education. Thus, four of the seven hypotheses were fully confirmed, two were partially confirmed, while one hypothesis was rejected. The profile of an employed person who, potentially, has the greatest chances of becoming an entrepreneur is the following: a younger man with a high school diploma (a degree does not have such a significant impact), who is employed in a private company, has previous entrepreneurial experience, is successful at work and has adequate finances.